Case Report on Cerebral Venous Thrombosis and Phenytoin Withdrawal - R, Vigneswaran; PM, Thenmozhi; P, Natarajan (Indian Journal of Pharmacy Practice)
The majority of patients with stroke who suffer from Cerebral Venous Thrombosis (CVT) are young people and children. Women have venous thromboembolism three times more frequently than men do. Cerebral Venous Thrombosis (CVT), a special site for thrombosis, is a specific cause of stroke. Compared to both arterial stroke and Venous Thromboembolism (VTE), CVT primarily affects children and young people. A variety of symptoms and indicators can be present in patients. The lateral, cavernous, and superior sagittal sinuses are the ones that thrombose the most commonly. Surgery, mechanical thrombectomy, anticoagulation, and fibrinolysis are available options. A 21-year-old woman with symptoms of rashes that have been present for two days, a history of cerebral venous thrombosis, phenytoin allergy, early papilledema, nausea, exertional dyspnea, and giddiness is the subject of the case study. The patient's medication regimen includes nicoumalone, levitracetam, acetazolamide, LMWH, pantaprazole, paracetamol, and cephalexin.
Keywords: CVT; Phenytoin allergy; Pappilledema; Hypoglycemia; Young age group